2010
DOI: 10.1007/bf03245880
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and proton transport properties of mixed metal phosphonate-zirconium titanium hydroxy ethylidene diphosphonate

Abstract: Novel hybrid material, zirconium titanium hydroxy ethylidene diphosphonate (ZTHEDP) of the class of tetravalent bimetallic acid (TBMA) salt was synthesized using sol-gel route. ZTHEDP was characterized for elemental analysis (zirconium, titanium and phosphorus by ICP-AES and carbon and hydrogen by CHN analyzer), spectral analysis (FTIR), thermal analysis (TGA), Xray diffraction studies and SEM. Chemical resistivity of this material was assessed in various media-acids, bases and organic solvents. The protons pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…The acidic character of the coordinated metal ions is related to ionic radii, charge, and coordinate site (phosphonic acids). Zr 4+ (0.86 Å) and Ti 4+ (0.74 Å) with smaller ionic radii and hence a high charge density shows higher proton conduction compared to cerium- and thorium-phosphonates (the bigger the cation, the higher the proton conductivity). , The observed specific conductivity trend is ZrHEDP (4.13 × 10 –4 ) > TiHEDP (1.34 × 10 –4 ) and ThHEDP (5.39 × 10 –6 ) > CeHEDP (8.30 × 10 –7 ). Further, the obtained E a values for ThHEDP (0.68 kcal·mol –1 ) and CeHEDP (0.14 kcal·mol –1 ) are a result of the contribution of such factors as discussed earlier in the text and low compared to ZrHEDP (2.36 kcal·mol –1 ) and TiHEDP (2.87 kcal·mol –1 ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The acidic character of the coordinated metal ions is related to ionic radii, charge, and coordinate site (phosphonic acids). Zr 4+ (0.86 Å) and Ti 4+ (0.74 Å) with smaller ionic radii and hence a high charge density shows higher proton conduction compared to cerium- and thorium-phosphonates (the bigger the cation, the higher the proton conductivity). , The observed specific conductivity trend is ZrHEDP (4.13 × 10 –4 ) > TiHEDP (1.34 × 10 –4 ) and ThHEDP (5.39 × 10 –6 ) > CeHEDP (8.30 × 10 –7 ). Further, the obtained E a values for ThHEDP (0.68 kcal·mol –1 ) and CeHEDP (0.14 kcal·mol –1 ) are a result of the contribution of such factors as discussed earlier in the text and low compared to ZrHEDP (2.36 kcal·mol –1 ) and TiHEDP (2.87 kcal·mol –1 ) .…”
Section: Resultsmentioning
confidence: 99%
“…The reports also demonstrate the way to investigate novel proton-conducting materials and to understand the conduction mechanism is now a prior demand, the promising use of these materials being in catalysis, fuel cells, sensors, and so forth. Earlier, we prepared amorphous M 4+ -phosphates and -phosphonates (M = Zr, Sn, and Ti) and studied their proton conduction behavior. , Literature survey shows that not much research has focused toward phosphonates of thorium (Th 4+ ) and cerium (Ce 4+ ). In our earlier report, we synthesized thorium and cerium phosphates and measured proton conductivity, where fairly good conductivity was observed in the range of ∼10 –7 S·cm –1 .…”
Section: Introductionmentioning
confidence: 99%
“…Products were claimed for the cleansing, polishing and pretreatment of metals as well as their application in adhesives, personal care products, pharmaceuticals, construction materials, fracturing fluids and dental implants. Furthermore, reaction products from zirconyl chloride with HEDP have been proposed as sorbents, 2 ion exchangers, 3,4 catalysts, [5][6][7] proton conductors 8 and recently as corrosion inhibitors for magnesium. 9 The complexation of zirconium from ZrOCl 2 with HEDP has been studied by Romanova et al by using titration and pH.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] The materials can be used as proton conductors and for the modification of surfaces because of their polar pores and different organic groups. [10][11][12][13][14][15][16] Zirconium(IV) phenylphosphonate was one of the first described metal phosphonates. 17 Cunningham et al showed different syntheses of divalent metal phenylphosphonates with the general formula M(II)(O 3 PC 6 H 5 )•H 2 O.…”
Section: Introductionmentioning
confidence: 99%